2004
DOI: 10.1007/s00403-004-0509-9
|View full text |Cite
|
Sign up to set email alerts
|

1?,25(OH)2D3 regulates NF-?B DNA binding activity in cultured normal human keratinocytes through an increase in I?B? expression

Abstract: NF-kappaB is a dimeric transcription factor which regulates transcription of a number of different genes including IL-8 and p53. In resting cells NF-kappaB is usually retained in an inactive state in the cytoplasm through binding to a member of the inhibitory kappaB (IkappaB) protein family. The purpose of this study was to determine the effect of 1alpha,25(OH)(2)D(3) on NF-kappaB activation in both unstimulated and stimulated (IL-1alpha) cultured normal human keratinocytes. NF-kappaB DNA binding activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 32 publications
2
48
1
Order By: Relevance
“…Treatment with calcitriol did not affect either the IkBa degradation or recovery. These results are at variance with another study showing that calcitriol upregulated IkBa protein and mRNA levels in keratinocytes (Riis et al, 2004). Examining the involvement of NFkB activation in the induction of MMP-9 by TNFa, we found that addition of a specific NFkB inhibitor 1 h after exposure to TNFa, after full recovery of IkBa levels, sufficed to abolish MMP-9 induction.…”
Section: Discussioncontrasting
confidence: 81%
“…Treatment with calcitriol did not affect either the IkBa degradation or recovery. These results are at variance with another study showing that calcitriol upregulated IkBa protein and mRNA levels in keratinocytes (Riis et al, 2004). Examining the involvement of NFkB activation in the induction of MMP-9 by TNFa, we found that addition of a specific NFkB inhibitor 1 h after exposure to TNFa, after full recovery of IkBa levels, sufficed to abolish MMP-9 induction.…”
Section: Discussioncontrasting
confidence: 81%
“…Because the VDR can interact directly with p65 (21), the most commonly held mechanism to explain vitamin D inhibition of NF-B is that the VDR-p65 interaction blocks the nuclear translocation of p65/p50 (10,26). This mechanism, however, cannot explain how 1,25(OH) 2 D 3 stabilizes IB␣, which was reported in many studies (10,12,14,17,18) and is well known as a critical step in the inhibition of NF-B. In fact, in many studies (14,26), including this one, VDR-p65 interaction was not detectable, suggesting that VDR-p65 interaction is weak, if there is any.…”
Section: Discussionmentioning
confidence: 68%
“…nuclear translocation, blocks NF-B DNA binding, increases IB␣ levels, or stabilizes IB␣ protein (10,12,14,15,17,18). It has also been shown that 1,25(OH) 2 D 3 suppresses RelB transcription (19) and reduces p105/p50 and c-rel protein levels (20).…”
mentioning
confidence: 99%
“…1,25(OH) 2 D 3 has also been shown to decrease the DNA binding capacity of NF-B in human fibroblasts (13). In human keratinocytes, 1,25(OH) 2 D 3 is able to reduce NF-B DNA binding activity by increasing I B␣ protein levels, which contributes to the reduction in IL-8 production (37). In pancreatic islet cells, a vitamin D analog is reported to significantly downregulate proinflammatory chemokine production, which is associated with upregulation of I B␣ transcription and arrest of NF-B p65 nuclear translocation (11).…”
mentioning
confidence: 99%